2022
DOI: 10.18295/squmj.4.2021.067
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of COVID-19 on Healthcare Workers

Abstract: Objectives: To assess anxiety and depression symptoms during the coronavirus pandemic among health care professionals in Pakistan. Methods: This is a cross-sectional study where a questionnaire containing demographics, and a validated fear scale, depression, and anxiety scale was made on Google drive and was sent to health care workers as doctors, nurses, and paramedical staff working in six different hospitals in Pakistan, through What's app on smartphones from May 1 to Jun 30, 2020. Data was analyzed on SPSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…A study conducted in six hospitals in Pakistan using the PHQ-9 and GAD-7 scales to evaluate 400 healthcare workers during the frst wave of COVID-19 revealed that 21.8% of them had moderate-to-severe anxiety or depression [29]. Similar results were found in a study conducted on 398 healthcare workers from Punjab, where the prevalence of anxiety and depression was 21.4% and 21.9%, respectively [30].…”
Section: Introductionsupporting
confidence: 68%
“…A study conducted in six hospitals in Pakistan using the PHQ-9 and GAD-7 scales to evaluate 400 healthcare workers during the frst wave of COVID-19 revealed that 21.8% of them had moderate-to-severe anxiety or depression [29]. Similar results were found in a study conducted on 398 healthcare workers from Punjab, where the prevalence of anxiety and depression was 21.4% and 21.9%, respectively [30].…”
Section: Introductionsupporting
confidence: 68%
“…This is like another study conducted in China whereby more people experienced stigma, and psychological distress, precisely posttraumatic stress disorder at 69.47% (95% confidence interval (CI): 66.81%-72.13%) of the measured Wuhan due to Covid-19 [8]. This looks like another study conducted in Pakistan whereby it was found that 21.8% of healthcare professionals suffered from moderate to severe depression symptoms, 15.5% from moderate to severe anxiety, and 65.5% from moderate symptoms of fear [9]. Also, another study in Chile aiming to determine the variables attributable to the fear of contracting Covid-19 demonstrated that the length of the pandemic has unquestionably affected the behavior of people and has generated fear in many people as there is an intensification in the risk of getting sick, exclusively after morbidity enlarged or one of the family members became ill or died.…”
Section: Discussionmentioning
confidence: 54%
“…Studies to date have reported that fear of COVID-19 had a significant relationship with age and was not related to work place. 38 , 39 Respondents from the UKDN believed their students were more worried than those from the UAE. However, this finding could be due to the reported number of COVID-19 cases at the time of the study as the data of the current study was collected in June and July of 2021, when the number of cases were rapidly increasing.…”
Section: Effect On Future Graduatesmentioning
confidence: 99%